Starting an Informal Presentation in the Wildland-Urban Interface - Martha C. Monroe; Lynn Weiss (EDIS)
FOR-111, a 4-page illustrated fact sheet by Martha C. Monroe and Lynn Weiss, highlights for extension agents the most important elements of starting successful presentations for homeowners. Includes references. Published by the UF School of Forest Resources and Conservation, April 2007.